Implementasi Bauran Komunikasi Pemasaran Pada Perusahaan Rokok Elektrik UPODS - Aloysius Mado; Davis Roganda Parlindungan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The The HPTL (Other Tobacco Processing) industry is experiencing a fairly rapid development of innovation and technology. These developments have resulted in competition between one company and another. With the development of information and communication technology, companies must be able to communicate their marketing effectively to disseminate information and attract consumers to make purchases related to the products of their company. This research uses descriptive qualitative research method with post-positivism paradigm. The results of this study indicate that UPODS implements a marketing communication mix through advertising, sales promotion, events and experiences, public relations and publications, direct and interactive marketing, and personal selling.